Development of PAI Game Learning Media to Improve Student Learning Outcomes - Astrifidha Rahma Amalia; Ikhsan Setiawan (Nusantara Education, 2023)
The purpose of the study is to describe the product design of learning media by game tajwid matching and the impact of using this learning media for Elementary School Level. The type of the research is Research and Development based on the model of ADDIE. Data collection technique that researcher used are questionnaire and test both pre-test and post-test. And data analysis was carried the content analysis, descriptive, and T-test. The result of research conducted by researchers can be concluded that: 1) The product of development is game of tajwid matching. The product has been validated by some experts i.e. learning material expert get the percentage of 92%, media design expert get the percentage of 88%, and from the teacher get the percentage of 88%. This mean that the game is fair enough to be implemented for learning process in the class. 2) The game of tajwid matching is effective to increase the learning result. The product proven significantly to improve the learning result and be able to be seen in the average of post test score is greater than post-test (77,42>94,84). Based on the T-test calculation resulted that tcount>ttable (7,2759494>2,036933334) means that Ha was accepted and Ho was rejected.